Limestone As Green Roof Media For Harvested Rainwater Improvement - Ramli, Muhammad Azlan (Universiti Sains Malaysia, 2021)
Urbanization has resulted in a substantial reduction of greenery. While we cannot stop urbanization, we can increase green coverage in urban development by incorporating green roofing. Generally, green roofs in urban environments have three essential functions: delay rainwater runoff, moderate building temperatures, and reduce the urban heat island effect (UHI). However, these essential functions only can be achieved by designing the green roofs system adequately based on the existing guidelines. This study highlighted the extensive green roof’s design criteria with the main focus on media filtration capacity and the efficiency of the green roof media in improving the harvested rainwater quality. For this research, limestone was used as the media with different sizes, classified as fine and coarse limestone. Based on the experiments conducted for the filtration capacity, coarse limestone permeability was higher than fine limestone. Meanwhile, several experiments were also conducted to determine the efficiency of limestone in treating rainwater. The chosen parameters are turbidity, colour, pH, COD, iron, zinc, total Kjeldahl nitrogen, and phosphorus. At the end of this research, it was found that fine limestone was more effective in improving the rainwater quality compared to coarse limestone due to the larger surface area and longer contact time between the limestone and the rainwater itself. The average percentage of pollutants removal for fine limestone is 35.75% for COD, 38.27% for iron, 54.73% for phosphorus, 90.85% for zinc, and the highest average percentage removal is up to 100% which is for TKN removal in rainwater.